2004
DOI: 10.1089/ees.2004.21.647
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Program Desorption Mass Spectrometry of PAHs from Mineral and Organic Surfaces

Abstract: This research investigated the release of polycyclic aromatic hydrocarbons (PAHs) from spiked materials using thermal desorption mass spectrometry. Experimental methods were developed to obtain real-time PAH desorption data through use of a thermal program desorption probe. Data analysis techniques were investigated to explore the thermal desorption profiles of milligram-size samples. Peak temperatures of desorption were observed to vary among PAHs and among sorbents. For the same absorbent, peak temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…These temperature ramp rates were chosen based on machine limitations (ramp rates from 10 to 100Њ/min in 10Њ increments) and previous work conducted by Talley et al [6], which found consistent results using a 10Њ/min temperature ramp rate. These temperature ramp rates were chosen based on machine limitations (ramp rates from 10 to 100Њ/min in 10Њ increments) and previous work conducted by Talley et al [6], which found consistent results using a 10Њ/min temperature ramp rate.…”
Section: Tpd Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These temperature ramp rates were chosen based on machine limitations (ramp rates from 10 to 100Њ/min in 10Њ increments) and previous work conducted by Talley et al [6], which found consistent results using a 10Њ/min temperature ramp rate. These temperature ramp rates were chosen based on machine limitations (ramp rates from 10 to 100Њ/min in 10Њ increments) and previous work conducted by Talley et al [6], which found consistent results using a 10Њ/min temperature ramp rate.…”
Section: Tpd Methodsmentioning
confidence: 99%
“…As recommended by Talley et al [6], all sample vials generally were filled to approximately one-eighth capacity to limit Thermal programmed desorption of PAHs on mineral sorbents interparticle-diffusional influences. Due to its lower density, kaolin sample vials were filled with slightly greater volume.…”
Section: Tpd Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the occurrence of PAHs in low-organic matter groundwater environments and supported by experimental studies, it is supposed that the mineral phase can play a significant role in the retention of PAHs in soils. A number of sorption studies were performed with pure, well characterized mineral sorbents [16][17][18][19][20][21][22]. There are several competing mechanisms used to explain the sorption of PAHs to the mineral surfaces.…”
Section: Introductionmentioning
confidence: 99%